Temperature Control of an Electric Through Virtual Hardware in the Loop Technique - Mollocana, Jéssica (2022)
This article presents the design of PID, fuzzy and MPC control algorithms for the temperature process of an electric oven with the objective of comparing operational and economic indexes. The controllers are implemented using the hardware in the loop technique that considers the virtualization of the process in the Unity 3D graphics engine. The development of the virtual environment incorporates 3D models that resemble a real environment of the brick manufacturing process, allowing the immersion and interaction of the user with the environment, in order to perform monitoring and control tasks of the industrial process. For the virtualization of the industrial process, it is considered to obtaining a mathematical model that represents the dynamics of the temperature plant. Finally, the experimental results achieved through the implementation of the hardware in the loop technique are presented, and a comparison of the controllers is performed in terms of power consumption, controller performance by visualizing the behavior of the temperature system and the evolution of the control errors.